Hydraulic characteristics of sedimentary deposits at the J-PARC proton-accelerator, Japan - Marui Atsunao; H. Gallardo Adrian (Earth Sciences Research Journal)
Hydraulic characteristics of sediments were investigated at J-PARC for the purpose of site characterization in relation with the construction of Japan's largest proton-accelerator. A total of 340 samples extracted from 9 exploratory wells were examined by standard laboratory tests and complemented with statistical analyses to quantitatively determine the main terrain attributes. Two main hydro-geological units were recognized, although a number of embedded layers defined a multilevel aquifer. Grain-size distribution derived from sieve analysis and the coefficient of uniformity showed that soils are poorly sorted. On the other hand, hydraulic conductivity was measured by a number of parameters such as a log-normal distribution. Conductivity was also predicted by empirical formulas, yielding values up to three orders of magnitude higher. Discrepancies were explained in terms of soil anisotropy and intrinsic differences in the calculation methods. Based on the Shepherd's approach, a power relationship between permeability and grain size was found at 2 wells. Hydraulic conductivity was also correlated to porosity. However, this nterdependence was not systematic and therefore, properties at many parts of the profile were considered to be randomly distributed. Finally, logs of electrical conductivity suggested that variations of soil hydraulic properties can be associated to changes in water quality. In spite of the remaining uncertainties, results yielded from the study are useful to better understand the numerical modelling of the subsurface system in the site.